Perception of seriousness and preventive health actions of patients with type 2 diabetes - Susanna C.D. Wright; Jacoba J.M. Jansen van Rensburg; Johanna E. Maree (AOSIS, 2009)
Diabetes mellitus is one of the most common chronic health conditions in the world. Though type 2 diabetes is a very serious condition, it is the complications that go with it that cause major morbidity and mortality. It is possible for a person with type 2 diabetes to lead a normal, happy life with the adequate treatment and motivation. The treatment involves increased physical activity, reducing weight if overweight, following a healthy diet and oral drugs or insulin injections. Patients deliver 95% of their care. According to the Health Promotion Model a nurse can support patients by focussing on the benefits of the treatment, teaching them to overcome management barriers and by giving positive feedback. The purpose of this study was to determine whether type 2 diabetes patients who were educated and counselled at a Centre for Diabetes in Limpopo Province, South Africa, perceive their condition as serious and change their lifestyle to prevent complications. The design was an exploratory, contextual, quantitative survey. A convenient sample (n=40) was chosen from patients attending the Centre for Diabetes. The data method was self-report using a pre-testing questionnaire and descriptive statistics to analyse the data. The results of the study indicate that though the majority of the groups' physical measurements were above normal (obesity 85%, hypertension 35%, HbA1c 65% and waist circumference 70%), they perceived the diabetes diagnosis as not serious (87.5%) and well controlled (87.5%). Solutions for educating individuals to change their lifestyles to prevent complications when they are feeling well have not yet been found. Opsomming Diabetes mellitus is 'n algemene chroniese gesondheidstoestand. Alhoewel tipe 2-diabetes 'n ernstige toestand is, veroorsaak komplikasies die meeste morbiditeit en mortaliteit. Dit is moontlik vir 'n persoon met tipe 2-diabetes om 'n normale, gelukkige lewe te lei met die nodige behandeling en motivering. Behandeling behels verhoogde fisiese aktiwiteit, gewigsverlies, 'n gesonde dieet en orale medikasie of insulienbehandeling. Pasiënte is egter verantwoordelik vir 95% van hul behandeling. Volgens die Gesondheidsbevorderingsmodel kan 'n verpleegkundige 'n pasiënt ondersteun deur te fokus op die voordele van behandeling, voorligting om probleme te oorkom en deur positiewe terugvoering. Die doel van die studie was om te bepaal of die pasiënte met tipe 2-diabetes wat voorligting en berading by 'n Sentrum vir Diabetes in Limpopo Provinsie ontvang, hul toestand as ernstig beskou en of hulle hul lewenswyse verander ten einde komplikasies te voorkom. Die ontwerp was 'n ondersoekende kwantitatiewe opname. Die gerieflikheidsteekproef was veertig deelnemers (n=40). Die data-insamelingsmetode was self-rapportering deur middel van 'n vraelys en die data is met behulp van beskrywende en statistiese analise ontleed. Die resultate dui daarop dat die meerderheid van die groep se fisiese lesings hoër as normaal was (oorgewig 85%, hipertensie 35%, HbA1c 65% en middellyn 70%). Die meeste van die deelnemers (87.5%) het hul diagnose van tipe 2 diabetes as nie ernstig nie en goed gekontroleerd beskou. Die oplossing oor hoe om mense te leer om hul lewenswyse te verander om komplikasies te voorkom terwyl hulle op die oomblik nog goed voel, is nog nie bepaal nie.